Evaluation of Cortical Bone Formation on Mandibular Condyle in Asymptomatic Adolescents and Young Adults Using Cone-Beam Computed Tomography - Yo-Seob Seo; Hyun-Jeong Park; Sun-Kyoung Yu; Seo-Rin Jeong; Ji-Won Ryu (Life, 2022)
The aim of this study was to evaluate cortical bone formation on the mandibular condyle using cone-beam computed tomography (CBCT) in asymptomatic adolescents and young adults and to evaluate the relationship between age and sex. CBCT images that can evaluate the shape of the mandibular condyle were selected from asymptomatic patients aged 13–25. The degree of cortication on the mandibular condyle (CMC) was evaluated using CBCT images reconstructed in the axial, sagittal, and coronal planes. CBCT data of 829 patients (413 males, 416 females) were selected and then the left and right images of all patients were acquired; consequently, a total of 1658 temporomandibular joint-related images were evaluated in this study. The degree of CMC was correlated with age in men and women (p < 0.05). The frequency of CMC 0 disappeared in woman aged 20 years and in men aged 21 years. Cortical bone formation of the mandibular condyle was completed at age 22 years in women and 24 years in men. The degrees of cortical bone formation of the mandibular condyle between men and women showed significant differences between the ages of 15–19 and 22 years. This difference can be interpreted as a different mandible growth period between the sexes.